Retinoic Acid Receptor-Related Receptor Alpha Ameliorates Autoimmune Arthritis via Inhibiting of Th17 Cells and Osteoclastogenesis - Park, Jin-Sil; Moon, Su-Jin; Lim, Mi-Ae; Byun, Jae-Kyeong; Hwang, Sun-Hee; Yang, SeungCheon; Kim, Eun-Kyung; Lee, Hohyun; Kim, Sung-Min; Lee, Jennifer; Kwok, Seung-Ki; Min, Jun-Ki; et al. (Frontiers in Immunology, 2019)
Rheumatoid arthritis (RA) is a chronic inflammatory polyarthritis characterized by progressive joint destruction. IL-17-producing CD4+ T (Th17) cells play pivotal roles in RA development and progression. Retinoic acid receptor-related orphan receptor alpha (RORα) is a negative regulator of inflammatory responses, whereas RORγt, another member of the ROR family, is a Th17 lineage-specific transcription factor. Here, we investigated the immunoregulatory potential of RORα in collagen-induced arthritis (CIA) mice, an experimental model of RA. Cholesterol sulfate (CS) or SR1078, a ligand of RORα, inhibited RORγt expression and Th17 differentiation in vitro. In addition, fortification of RORα in T cells inhibited the expression levels of glycolysis-associated genes. We found that RORα overexpression in CIA mice attenuated the clinical and histological severities of inflammatory arthritis. The anti-arthritis effect of RORα was associated with suppressed Th17 differentiation and attenuated mTOR-STAT3 signaling in T cells. Furthermore, altered RORα activity could directly affect osteoclastogenesis implicated in progressive bone destruction in human RA. Our findings defined a critical role of RORα in the pathogenesis of RA. These data suggest that RORα may have novel therapeutic uses in the treatment of RA.